Barriers to Mental Health Treatment in Rural Older Adults - Brenes, Gretchen A. (Am J Geriatr Psychiatry, 2015)
OBJECTIVES: The purpose of this study was to identify the barriers to seeking mental health treatment experienced by rural older adults. We also examined if barriers differed by age and worry severity. METHODS: Participants were 478 rural older adults responding to a flyer for a psychotherapy intervention study. Interested participants were screened by telephone, and barriers to mental health treatment were assessed. Participants completed a demographic questionnaire and the Penn State Worry Questionnaire-Abbreviated. RESULTS: The most commonly reported barrier to treatment was the personal belief that "I should not need help". Other commonly reported barriers included practical barriers (cost, not knowing where to go, distance), mistrust of mental health providers, not thinking treatment would help, stigma, and not wanting to talk with a stranger about private matters. Multivariable analyses indicated that worry severity and younger age were associated with reporting more barriers. CONCLUSIONS: Multiple barriers interfere with older adults seeking treatment for anxiety and depression. Older age is associated with fewer barriers, suggesting that the oldest old may have found strategies for overcoming these barriers. Young-old adults may benefit from interventions addressing personal beliefs about mental health and alternative methods of service delivery.